Economics of monetary union. 12th ed. - De Grauwe, Paul (New York, 2018)
"The twelfth edition of Economics of Monetary Union provides a concise analysis of the theories and policies relating to monetary union. The author addresses current issues surrounding the Eurozone, including; a critical discussion of the costs and benefits of possible exits by its member countries, an analysis of the role of the ECB as new single supervisor and detail on the sovereign debt crisis.